The Topography of Brain Microstructural Damage in Amyotrophic Lateral Sclerosis Assessed Using Diffusion Tensor MR Imaging - Canu, E. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: ALS leads to macrostructural (ie, cortical atrophy and hyperintensities along the corticospinal tract) and microstructural (ie, gray matter intrinsic damage) central nervous system abnormalities. We used a multimodal voxelwise imaging approach to assess microstructural changes independent of macrostructural volume loss in patients with ALS compared with HCs. MATERIALS AND METHODS: Twenty-three patients with ALS and 14 HCs were studied. Conventional imaging and DTI were performed. Images were processed by using SPM5 to assess measures of gray and white matter atrophy as well as microstructural damage (ie, MD and FA). DTI alterations independent of volume loss were investigated. RESULTS: When we accounted for both gray and white matter atrophy, patients with ALS showed increased MD values in several gray and white matter areas mainly located in the orbitofrontal and frontotemporal regions bilaterally, in the right genu of the corpus callosum, and in the right posterior limb of the internal capsule. When we accounted for white matter volume loss, patients with ALS showed decreased FA along the corticospinal tract bilaterally and in the left inferior frontal lobe relative to HCs. The MD of the orbitofrontal regions bilaterally was associated significantly with disease duration. CONCLUSIONS: In patients with ALS, DTI detects microstructural changes independent of brain tissue loss. The affected regions included both motor and extramotor areas. The extent of ALS-related DTI abnormalities was greater than that disclosed by the volumetric analysis.